Casa ou dinheiro? Modelos de decisão de famílias em áreas de risco - Matos Filho, Eduardo de Souza (2019)
The Government of the State of Ceará has sought to remove the population from flooded areas, offering them housing units built by the program “Minha Casa Minha Vida” from the Federal Government or compensation in cash, according to the option of each family. We sought to investigate, in an exploratory way, what factors influence the decision making of a family, related to the characteristics of the property offered, of the removed property, and of the family itself. To this end, data from the report of the Rio Cocó Urban and Environmental Improvement Program, together with the Rio Cocó Social Technical Work report, were analyzed using qualitative response regression models (logit). The results show that the logic of the best financial return alone does not regularly define user behavior, as users often make decisions that challenge this logic. Affective values attributed to better built properties seemed to influence the choice of benefit. It is noted that the highest preference for Housing Units occurs by female users, without stable union bond and inhabitants of low constructive real estate. This preference also tends to grow as the distance to Residencial José Euclides increases and the smaller the distance to Residencial Cidade Jardim.